PENGARUH GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN - Indi Hia Rahayu; Suciati Muanifah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze and compare the findings of four scholarly articles discussing the impact of green accounting on financial performance. The method used is a literature review with a content analysis approach, focusing on articles published between 2020 and 2024. Some studies found no significant impact between the implementation of green accounting and financial performance, while others showed a positive impact, particularly in the disclosure of environmental costs. These differing results are attributed to variations in measurement indicators and the industries studied. Nevertheless, the implementation of green accounting provides long-term benefits in improving a company's reputation and attracting investor attention. Therefore, companies are advised to prioritize the implementation of green accounting as part of their corporate social responsibility.